GAMBARAN KASUS KEMATIAN AKIBAT KECELAKAAN LALU LINTAS DI RSUD ABDOEL WAHAB SJAHRANIE TAHUN 2020-2022 (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Samarinda has the highest fatality rate attributed to road accidents in the East Kalimantan from 2018 to 2020. This study analyzes of the deaths caused by traffic accidents, using data obtained from medical records and/or Visum et Repertum (VeR) of victims at RSUD Abdoel Wahab Sjahranie from 2020 to 2022. This study is a descriptive cross-sectional approach a total sampling technique. A total of 110 samples were included in the investigation. According to the statistics, the majority of the casualties, specifically 78.18% were male, 34,55% were aged 12-25 years, 60,91% were employed, and 71.82% were motorcycle riders. The medical records predominantly report cranial traumas (87.21%) and fractures (74.42%) as the characteristic injuries. In contrast, the injuries recorded in VeR mostly comprise at the lower extremity (96.00%), abrasions (92.00%), and open wounds (92.00%) being the most prevalent, uneven wound edges (78.26%), injuries involving bones (56.52%), and incidents of skull fractures (36.00%). The time interval of victims' deaths is predominantly within 3-30 days (52.73%). According to this study, it can be deduced that most victims are those with a high degree of mobility. The injuries documented in both medical records and VeR display different features. The fatalities predominantly transpire within 3-30 days.